PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) DAPAT MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 007 RUMBIO JAYA - Desi Susanti; Syahrifuddin '; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this study was to determine whether the implementation of Problem Based Learning model to improve students’ achievement in the subject of Science fourt year students of state elementary school 007 Rumbio Jaya. Formulation of the problem in this study is whether the implementation of Problem Based learning model improve students’ achievement in the subject of Science fourt year students of state elementary school 007 Rumbio Jaya.? This research is Classroom Action Research which carried with two cycles, each cycle was conducted over two sessions. Subjects in this study students of fourth year students of state elementary school 007 Rimbo Panjang the number of students as many as 20 students consisted 14 male and 6 female. Data collection techniques in this study there are three, namely observation, testing, and documentation. Based on the results of the study showed an increase in student learning outcomes. In the prior action completeness students achieve 45% or 9 complete student, the students who complete the first cycle increased to 15 people or completeness reaches 75%. In the second cycle students achieve mastery turns 18 students or with the percentage of 90%. Thus it can be concluded that with the implementation of Problem Based learning model improve students’ achievement in the subject of Science fourt year students of state elementary school 007 Rumbio Jaya.Key Words : Problem Based Learning Model, and students’ achievement in the subject of Science